2017
DOI: 10.1353/hpu.2017.0026
|View full text |Cite
|
Sign up to set email alerts
|

Public Housing Relocations and Relationships of Changes in Neighborhood Disadvantage and Transportation Access to Unmet Need for Medical Care

Abstract: Introduction Cross-sectional research suggests that neighborhood characteristics and transportation access shape unmet need for medical care. This longitudinal analysis explores relationships of changes in neighborhood socioeconomic disadvantage and transportation access to unmet need for medical care. Methods We analyzed seven waves of data from African American adults (N = 172) relocating from severely distressed public housing complexes in Atlanta, Georgia. Surveys yielded individual-level data and admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Because a prior study suggested that environmental factors can either facilitate or hamper medical care utilization [ 29 ], we assessed neighborhood environment using the Japanese version of the International Physical Activity Questionnaire Environment Module (IPAQ-E) [ 30 ]. To evaluate neighborhood environment related to ME, we used two items from IPAQ-E: access to public facilities including medical institutions and access to public transport.…”
Section: Methodsmentioning
confidence: 99%
“…Because a prior study suggested that environmental factors can either facilitate or hamper medical care utilization [ 29 ], we assessed neighborhood environment using the Japanese version of the International Physical Activity Questionnaire Environment Module (IPAQ-E) [ 30 ]. To evaluate neighborhood environment related to ME, we used two items from IPAQ-E: access to public facilities including medical institutions and access to public transport.…”
Section: Methodsmentioning
confidence: 99%
“…6 Unmet social needs such as inadequate housing, food insecurity, and unemployment have been related to physical and mental health problems, shorter life expectancy, and increased health care utilization and costs. [7][8][9][10][11][12][13][14][15][16][17] Evidence of the impact of social factors on health outcomes and health care cost is prompting providers to develop models and implement interventions that incorporate patients' social needs into standard care. Models include educating medical students on social determinants of health, 18 and developing a culture in which assessing and addressing social determinants of health is considered part of high-quality primary care.…”
Section: Introductionmentioning
confidence: 99%
“…10 People without insurance are more likely to report poor access to health care (e.g., not having a primary care provider) and unmet needs for health care. 8, 11 Poor health care access may promote ongoing STI transmission and endemicity by increasing the proportion of the population with untreated STIs, thereby increasing the likelihood that a woman will be exposed to an infected sexual partner. 5 People with or at increased risk for HIV and other STIs tend to live closer to their sexual partners than do people from lower risk populations, 12 and a growing body of research suggests that features of the social (e.g., neighborhood socioeconomic advantage) and built (e.g., health care infrastructure) environment are associated with STIs as well as unmet needs for health care.…”
Section: Introductionmentioning
confidence: 99%
“…5 People with or at increased risk for HIV and other STIs tend to live closer to their sexual partners than do people from lower risk populations, 12 and a growing body of research suggests that features of the social (e.g., neighborhood socioeconomic advantage) and built (e.g., health care infrastructure) environment are associated with STIs as well as unmet needs for health care. 11, 1315 To date, no multilevel studies have explored relationships between neighborhood-level health care access and STIs. An understanding of whether and how neighborhood health care access is associated with having an STI can inform local STI prevention programming and structural interventions, including health care policy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation